2020
DOI: 10.1111/jog.14178
|View full text |Cite
|
Sign up to set email alerts
|

High post‐treatment serum soluble receptor‐binding cancer antigen expressed on SiSo cells (sRCAS1) levels is associated with poor survival of patients with cervical cancer

Abstract: Aim Receptor‐binding cancer antigen expressed on SiSo cells (sRCAS1) is responsible for induction of selective immunosuppression. In addition, preclinical studies have shown that sRCAS1 levels may reflect cancer aggressiveness. The main aim of our study was to analyze pre‐ and post‐treatment levels of sRCAS1 in the sera of patients treated for cervical cancer and to evaluate whether the levels change during treatment and their impact on patient prognosis. Methods The study included 49 patients suffering from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…in fact, rcaS1 expression is related to malignant characteristics, such as tumor size, invasion depth, clinical stage and poor overall survival. Thus, a number of clinical studies have reported the clinical importance of rcaS1 (20)(21)(22)(23)(24)(25)(26). By contrast, there have been few basic studies of the biological functions of rcaS1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in fact, rcaS1 expression is related to malignant characteristics, such as tumor size, invasion depth, clinical stage and poor overall survival. Thus, a number of clinical studies have reported the clinical importance of rcaS1 (20)(21)(22)(23)(24)(25)(26). By contrast, there have been few basic studies of the biological functions of rcaS1.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have shown the clinical significance of RCAS1 as a biomarker for the diagnosis and prognosis of malignant human tumors. RCAS1 expression has been observed in various malignant tumors and is correlated with poor prognosis of cancer patients; serum RCAS1 levels are also found to be significantly higher in cancer patients compared with healthy blood donors ( 21 25 ). Soluble-form RCAS1 has been shown to induce apoptosis in various human cell lines including normal peripheral lymphocytes, such as T and B cells and natural killer cells ( 19 , 26 ).…”
Section: Introductionmentioning
confidence: 99%